Barreras, Técnicas IA y Tecnologías IoT relacionadas en la Salud Pública en Zonas Rurales: Una Revisión de la Literatura - Chavez, Andres (2025)
The problems solution related to health care in rural areas have been very limited and deficient for years, and despite the advance of technologies, there is still a gap in finding a solution to mitigate this problem. Therefore, in this study, a systematic review of the literature on recent studies related to public health in rural areas was carried out. Five phases were used: planning, development, review results, taxonomic analysis and cross analysis. And 3 research questions were posed: what are the barriers affecting rural healthcare access, what AI algorithms were used to mitigate rural public health access difficulties, and what IoT devices were used to mitigate rural public health access difficulties. The results showed that: (1) the “barrier” that most affects access to public health in rural areas was “Human resources”, (2) the “AI algorithms” most used to mitigate the difficulties of access to public health in rural areas were ‘SVM’ and “Decision Tree” and the “IoT devices” most used to mitigate the difficulties of access to public health in rural areas was “Integrated Data Management”.  Finally, the result of the cross-analysis between “Barriers” and “IoT devices” showed that there is a large gap to be filled in two barriers: “reliability of sensors” and “culture”.